Decisive factors for indie publishers to win authors' hearts to publish their books - Anjaningrum, Widiya Dewi; Rahayu, Elisa Dwi; Viloria, Vivien Amor (Jurnal Siasat Bisnis, 2026)
Purpose – This study aimed to determine the significant impact of marketing stimuli on perceived usefulness, the appreciably effect of social media interaction on content quality, and the remarkably influence of perceived usefulness and content quality on purchase intentions.Design/methodology/approach – This is quantitative research, where quantitative data were obtained from the distribution of online questionnaires. The research sample was all participants of the "Book Writing Camp" up to Batch 21 (2023) who had published their books at PT. Litera Media Tama, totaling 162 people. A sophisticated PLS-SEM analysis was used to examine the data gathered.Findings – The results showed that perceived usefulness and content quality on the publisher's social media greatly determine the author's choice. To increase perceived usefulness, publisher must strengthen marketing stimuli such as relative service innovation, service and price advantage, and promotional effort. Meanwhile, publisher must interact more with consumers on social media to improve content quality.Research limitations – Limitations of this study are that the data collecting process was conducted online and only at one publisher. Therefore, the results obtained from this study may vary if applied to other publishers.Practical implications – Publishers should optimize marketing stimuli to strengthen perceived usefulness and increase interaction with followers on social media to improve content quality. Therefore, publishers can effectively attract very motivated writers to publish their books with that publisher.Originality/value – The originality of this work lies in the utilization of Planned Behaviour Theory inside a sophisticated conceptual framework that has yet to be employed in prior research. In addition, the framework tested on Indie publishers in developing countries, a practice that has yet to be explored.